PERENCANAAN DAN PENGEMBANGAN ARSITEKTUR PELAYANAN INFORMASI ALUMNI PADA UNIVERSITAS YAPIS PAPUA - JAYAPURA - Riandi Widiantoro; Kusrini Kusrini; Sudarmawan Sudarmawan (Universitas Janabadra, 2018)
The importance of the role of technology and information systems within the organization to support business activities so as to provide services in accordance with organizational goals, IKA Uniyap is an alumni development organization of Yapis University of Papua, in carrying out its role of IKA Uniyap has not fully utilized the information system.The togaf framework is a method that is able to design and manage technology architecture and information system so that it can describe a good architectural model and can be used by the organization to achieve the goal.The discussion in this research is making documentation of technology architecture planning and information system of alumni service of Yapis University of Papua using togaf framework, with result of discussion that is scope of business process covering 2 main activity and supporting, defining architectural principles and vision, mapping business strategy solution, defining current business conditions and proposed target business architecture, information systems architecture and technology architecture. Keyword: Arsitektur bisnis, Arsitektur sistem informasi, arsitektur teknologi, TOGAF ADM